Natural element method for the simulation of structures and processes - Chinesta, Francisco; Cescotto, Serge; Cueto, Elias; Lorong, Philippe (London : ISTE ; Hoboken, N.J. : Wiley, 2011)
"This book presents a recent state of the art on the foundations and applications of the meshless natural element method in computational mechanics, including structural mechanics and material forming processes involving solids and Newtonian and non-Newtonian fluids"--
Includes bibliographical references (p. [227]-238) and index.
Keywords: Materials -- Mechanical properties -- Mathematical models; Numerical analysis; Numbers, Natural; MATHEMATICS / Applied